Drag correlation for dilute and moderately dense fluid-particle systems using the lattice Boltzmann method. (January 2015) - Bogner, Simon; Mohanty, Swati; Rüde, Ulrich
Highlights: A numerical study of drag law for spherical particles in flow is presented. The study includes Reynolds numbers from close to zero up to 300. The results are compiled into a drag relation valid for the whole parameter range. We employ a two-relaxation-time lattice Boltzmann model for reliable simulations. A comparison is drawn between previous studies and the present. Abstract: This paper presents a numerical study of flow through static random assemblies of monodisperse, spherical particles. A lattice Boltzmann approach based on a two relaxation time collision operator is used to obtain reliable predictions of the particle drag by direct numerical simulation. From these predictions a closure law F ( Re p, φ ) of the drag force relationship to the bed density φ and the particle Reynolds number Re p is derived. The present study includes densities φ ranging from 0.01 to 0.35 with Re p ranging up to 300, that is compiled into a single drag correlation valid for the whole range. The correlation has a more compact expression compared to others previously reported in literature. At low particle densities, the new correlation is close to the widely-used Wen & Yu – correlation. Recently, there has been reported a discrepancy between results obtained using different numerical methods, namely the comprehensive lattice Boltzmann study of Beetstra et al. (2007) and the predictions based on an immersed boundary – pseudo-spectral Navier–Stokes approach (Tenneti et al., 2011). The present study excludes significant finite resolution effects, which have been suspected to cause the reported deviations, but does not coincide exactly with either of the previous studies. This indicates the need for yet more accurate simulation methods in the future.